Synthesis of 2-Thioaldoses via BF3-Promoted Cycloaddition of β-Methoxyvinyl Sulfides with 2,3-O-Isopropylidene Derivatives of aldehydo-Aldoses - Sugimura, Hideyuki; Kusakabe, Kousuke (Synlett, 2013)
A highly stereoselective approach to the synthesis of 2-thioaldose derivatives via BF3-promoted cycloaddition of β-methoxyvinyl sulfides with 2,3-O-isopropylidene derivatives of aldehydo-aldoses is described.
Keywords: aldehydes; boron; carbohydrates; cycloaddition; sulfur